Phosphor–Aluminum Composite for Energy Recycling with High‐Power White Lighting. Issue 19 (31st July 2017) - Park, Jehong; Kim, Jongsu; Kwon, Hansang
Abstract : A state‐of‐the‐art solid‐state lighting (SSL) device comprises a blue light‐emitting device covered with a yellow‐emitting phosphor. In a high‐power SSL device, thermal stability is an essential requirement for the phosphor because the phosphor is constantly irradiated with high‐power blue light, which causes thermal degradation. In this work, a thermally robust phosphor–aluminum composite (PAC) fused with low‐melting glass is introduced. The PAC exhibits a high thermal conductivity of 31.6 W m −1 K −1 and the PAC combined with a 4 W blue laser diode (LD) exhibits excellent thermal stability in luminous flux and chromaticity. Furthermore, energy is recycled in the PAC during lighting by coupling to a thermoelectric (TE) module. In the PAC‐TE system, the output voltage and current reveal 289 mV and 77 mA, respectively, at an output of 430 lumens under a 4 W blue LD. The results provide a starting point for further research in the composite‐material design for energy recycling with high‐power white lighting. Abstract : A phosphor–aluminum composite (PAC) for high‐power lighting is introduced. The PAC shows excellent thermal stability combined with a high‐power blue laser diode (LD). The possibility of energy recycling in a high‐power white‐lighting system using the PAC material, a thermoelectric module, and a high‐power blue LD is demonstrated.